2012
DOI: 10.1007/s00439-012-1240-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive natural selection of TRIB2, a novel gene that influences visceral fat accumulation, in East Asia

Abstract: Accumulation of visceral fat increases cardiovascular mortality in industrialized societies. However, during the evolution of the modern human, visceral fat may have acted as energy storage facility to survive in times of famine. Therefore, past natural selection might contribute to shaping the variation of visceral fat accumulation in present populations. Here, we report that the gene encoding tribbles homolog 2 (TRIB2) influenced visceral fat accumulation and was operated by recent positive natural selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…Taken together, these findings suggest that CDKAL1 may be one of the key energy metabolism genes targeted by recent selection. 4,50,51 Investigation of this novel locus of selection using targeted-sequencing may provide new insights in the pathogenesis of diabetes and metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that CDKAL1 may be one of the key energy metabolism genes targeted by recent selection. 4,50,51 Investigation of this novel locus of selection using targeted-sequencing may provide new insights in the pathogenesis of diabetes and metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Nakayama et al . [30] previously identified TRIB2 (tribbles pseudokinase 2) , which is related to visceral fat and obesity. Their results may have also suggested that gene polymorphism of TRIB2 was shaped by cold climatic conditions in East Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Another variant, the PC-1 Gln121, was also considered as a possible thrifty gene supported by studies in African and other groups (Rey et al 2012). A recent study provides evidence for a positive selection of TRIB2 gene, which influences visceral fat accumulation in East Asians (Nakayama et al 2013). In addition to these few examples showing a possibly positive selection in our evolutionary history with metabolic traits, others loci have been extensively studied, one of them being the LCT gene, at ~7,000 years bp, which is considered a prototypic example of selective advantage leading to rapid human evolution compatible with the agricultural innovations (Bersaglieri et al 2004).…”
Section: Evolutionary Explanations For Obesitymentioning
confidence: 99%